Notary Role in Making a Murabahah Account in Shari’a Banks - Etri Silviyanti; Gunarto Gunarto (Sultan Agung Notary Law Review, 2020)
This study aims to determine and analyze the terms of the Murabahah financing agreement according to Islamic law and the role of the notary in making Murabahah financing agreement in Islamic banks. The type of research used is descriptive analytical which aims to parse the facts to obtain an overview, about the existing problems, examine and study legal facts. The results of the study concluded that under the terms of the Murabahah financing agreement on a Shari’a bank according to Islamic law must meet the pillars and conditions as described in Compilation of Shari’a Economic Law and the role of a notary in making Murabahah agreement deeds in Islamic banks, it is needed as a party of legality (legal force) and in making Murabahah deeds in Islamic banks that are notarized the formulation must be in accordance with Article 38 of the Law on the Position of Notary without leaving Shari’a principles as well as the mechanism/procedure for making notarial deeds.